2016
DOI: 10.1039/c5nj02775f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell cytotoxicity profile and morphological response to polyoxometalate-stabilised gold nanoparticles

Abstract: The size and redox properties of molecular polyoxometalates (POMs) make them extremely relevant for bioapplications: from disrupting tumour growth and enzyme inhibition, to DNA-intercalating agents and antimicrobial applications. Their unique ability to reversibly dominate and receive electrons, coupled with their high anionic charge, also makes them suitable for the preparation of zero-valent state metal nanoparticles (NPs) from molecular precursors. Polyoxometalate-stabilised nanoparticles (NPs@POM) are ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…For Vero cells incubated with polyoxometalate-stabilized gold nanoparticles for 24h was from 20-100µg/mL, approximately 93-95% was shown to be alive, 0.1-0.3% apoptotic. This data is commensurate with little or no toxicity when compared to the control sample (Gabas et al, 2016). The synthesis of metal silver nanoparticles effect to Vero cell lines was found to be 18.15µg/mL.…”
Section: Cytotoxicity Of Cobalt(ii) Chloride To Vero Cellsupporting
confidence: 62%
“…For Vero cells incubated with polyoxometalate-stabilized gold nanoparticles for 24h was from 20-100µg/mL, approximately 93-95% was shown to be alive, 0.1-0.3% apoptotic. This data is commensurate with little or no toxicity when compared to the control sample (Gabas et al, 2016). The synthesis of metal silver nanoparticles effect to Vero cell lines was found to be 18.15µg/mL.…”
Section: Cytotoxicity Of Cobalt(ii) Chloride To Vero Cellsupporting
confidence: 62%
“…The few studies addressing the effect of POMs in melanoma, with most of them using B16 murine melanoma cells, reported a decrease in cell viability and antitumor activity [50,51], as well as impaired cellular tyrosinase activity and melanin formation [52]. More recently, encapsulated polyoxomolybdates and POTs were also studied in murine melanoma [52,53]. Selective cytotoxic tendencies were observed against murine cells causing necrotic cell death, probably due to the disruption of plasma membranes and antiproliferative cell cycle arrest in the gap (G 0 /G 1 ) and G 2 /mitosis (M) phases [53].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, encapsulated polyoxomolybdates and POTs were also studied in murine melanoma [52,53]. Selective cytotoxic tendencies were observed against murine cells causing necrotic cell death, probably due to the disruption of plasma membranes and antiproliferative cell cycle arrest in the gap (G 0 /G 1 ) and G 2 /mitosis (M) phases [53]. In the present study, we firstly confirmed the highest expression level of AQP3 in a human melanoma cell line, in agreement with the human tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, for minimizing the toxicity of POMs to normal cells, studies have indicated reduced POM toxicity through discovering of new POMs [12], such as encapsulating POMs in biomaterials (such as zeolites and biodegradable/biocompatible hydrogels) [13, 14], and conjugating POMs with organic ligands [15]. Technically, these strategies improve POMs’ biocompatibility [16], allow selective recognition of biological targets [17], and tune the bioactivity and cytotoxicity of POMs [18, 19]. Unfortunately, using POMs for therapy is still in its infancy; the most current research assesses the toxicity of POMs in vitro [12, 19, 20], rarely POM products have been evaluated for their toxic side effects in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, these strategies improve POMs’ biocompatibility [16], allow selective recognition of biological targets [17], and tune the bioactivity and cytotoxicity of POMs [18, 19]. Unfortunately, using POMs for therapy is still in its infancy; the most current research assesses the toxicity of POMs in vitro [12, 19, 20], rarely POM products have been evaluated for their toxic side effects in vivo. More importantly, investigation of acute and subchronic toxicity is essential before the development of POMs for clinical trials, because of the mechanism and consequence of toxicity in vivo was different from that of in vitro.…”
Section: Introductionmentioning
confidence: 99%